Relation between Corporate Governance and Accounting Quality - Pan, Yawen (2018)
Countless financial scandals from last century remind us to concentrate on this serious problem. Their reasons and their methods are hot topics in business management. This dissertation analyzes the factors that will influence financial frauds, and attempt to find out the relationship between corporate governance and financial frauds. 200 Chinese examples are used in this research, half of them are firms with frauds and half are not. Through comparing these two kinds of companies in some specific governance factors, we want to conclude the key elements that will significantly related with financial frauds and provide some ideas in improving corporate governance. Through the results of this study, independent directors, committees and efficient internal control systems are good tools to prevent misrepresentation of financial statements.